Infrared divergences and non-lightlike eikonal lines in Sudakov processes - Collins, J; Hautmann, F (2000)
We propose a method to analyze infrared contributions to non-inclusive processes in QCD. We use the one-loop Sudakov form factor as a working example. Borrowing techniques from renormalization theory, we construct counterterms for the contributions from the soft and collinear regions, and we relate them to eikonal Wilson lines taken along non-lightlike directions. (C) 2000 Published by Elsevier Science B.V.